A study on customer satisfaction toward UMW Pennzoil website as lead generators marketing / Mohd Fairuz Hussin - Hussin, Mohd Fairuz (Faculty of Business and Management, 2009)
Over the years, UPD has established a strong presence in lubricants industries. The Pennzoil products are well-know for heavy industries users. Today, UPD has taken a new step in the era of e-commerce by using latest technology which is internet as main marketing tolls. The main purpose of this research is to determine customers’ satisfaction toward UPD website or portal. Respondents in this research include 40 customers which are individual and company representative. These customers were given structured questionnaires via email, fax, and direct interviews. SERVQUAL by Parasuraman had been adopted in order to determine the key dimension that effect customers satisfaction which is Tangibles, Access, and Communication. The response from the questionnaire was statistically analyzed using the statistical tools (SPSS version 14.0). The findings showed that majority of the respondents were males, aged between 21 to 30 years old with main language spoken Bahasa Malaysia, and possess High School level of education. In reliability analysis, it can be seen that customers’ satisfaction, tangibles, access, and communication are acceptable because all of the results are 0.84, 0.85, 0.86 and 0.72 respectively. The findings from correlation and regression analysis indicate that all dimensions have strong and very strong relationship with customers’ satisfaction in UPD.